2014
DOI: 10.1055/s-0033-1361927
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Transfer to the Deltoid Muscle Using the Nerve to the Long Head of the Triceps with the da Vinci Robot: Six Cases

Abstract: The advantages of robotic microsurgery are motion scaling and disappearance of physiological tremor. Reasons for failure of the endoscopic technique could be explained by insufficient pressure. We had no difficulty using the robot without the sensory feedback. The robot-assisted nerve transfer to deltoid muscle using the nerve to the long head of the triceps was a feasible application for restoration of shoulder abduction after brachial plexus or axillary nerve injury. Therapeutic Study. Level of Evidence IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…There have been many preclinical studies conducted on animal and human cadaveric models discussing the feasibility of robotic-assisted peripheral nerve surgery, and clinical studies on the use of robot have been performed mostly on brachial plexus reconstructions. 15,19,25 In 2011, Mantovani et al performed the first exploration of supraclavicular brachial plexus and upper trunk reconstruction with nerve graft on a human cadaveric model. 26 In 2012, Garcia et al demonstrated three clinical brachial plexus reconstructions with robotic surgery, 27 two Chuang's level I avulsions from C6-T1 and C5-T1 and a C5-7 rupture.…”
Section: Brachial Plexus Reconstruction (►Table 1)mentioning
confidence: 99%
“…There have been many preclinical studies conducted on animal and human cadaveric models discussing the feasibility of robotic-assisted peripheral nerve surgery, and clinical studies on the use of robot have been performed mostly on brachial plexus reconstructions. 15,19,25 In 2011, Mantovani et al performed the first exploration of supraclavicular brachial plexus and upper trunk reconstruction with nerve graft on a human cadaveric model. 26 In 2012, Garcia et al demonstrated three clinical brachial plexus reconstructions with robotic surgery, 27 two Chuang's level I avulsions from C6-T1 and C5-T1 and a C5-7 rupture.…”
Section: Brachial Plexus Reconstruction (►Table 1)mentioning
confidence: 99%
“…Most recently, robot-assisted neurotization of deltoid muscle using the nerve to the long head of the triceps was described as a feasible application for the restoration of shoulder abduction after brachial plexus or axillary nerve injury. [7] These results demonstrate that telemicrosurgery allows very safe and precise peripheral nerve repairs by counteracting physiological tremor and by improving the view of the surgical field.…”
Section: What Has Been Done Until Now?mentioning
confidence: 69%
“…First, when performing electromyography, the axillary‐innervated variation of the LHT may cause misdiagnosing axillary neuropathy as posterior cord lesion or cervical radiculopathy. Second, the nerve to the LHT, which is considered as a potential donor for nerve transfer in upper brachial plexus injuries, 21‐24 might not be an appropriate source for this nerve transfer technique if it is derived from the axillary nerve. Therefore, preoperative electromyography should include the LHT to confirm whether the nerve to the LHT could be a proper donor for nerve transfer.…”
Section: Discussionmentioning
confidence: 99%